Cascading effects from plants to soil microorganisms explain how plant species richness and simulated climate change affect soil multifunctionality. (9th October 2018) - Valencia, Enrique; Gross, Nicolas; Quero, José L.; Carmona, Carlos P.; Ochoa, Victoria; Gozalo, Beatriz; Delgado‐Baquerizo, Manuel; Dumack, Kenneth; Hamonts, Kelly; Singh, Brajesh K.; Bonkowski, Michael; Maestre, Fernando T.
Abstract: Despite their importance, how plant communities and soil microorganisms interact to determine the capacity of ecosystems to provide multiple functions simultaneously (multifunctionality) under climate change is poorly known. We conducted a common garden experiment using grassland species to evaluate how plant functional structure and soil microbial (bacteria and protists) diversity and abundance regulate soil multifunctionality responses to joint changes in plant species richness (one, three and six species) and simulated climate change (3°C warming and 35% rainfall reduction). The effects of species richness and climate on soil multifunctionality were indirectly driven via changes in plant functional structure and their relationships with the abundance and diversity of soil bacteria and protists. More specifically, warming selected for the larger and most productive plant species, increasing the average size within communities and leading to reductions in functional plant diversity. These changes increased the total abundance of bacteria that, in turn, increased that of protists, ultimately promoting soil multifunctionality. Our work suggests that cascading effects between plant functional traits and the abundance of multitrophic soil organisms largely regulate the response of soil multifunctionality to simulated climate change, and ultimately provides novel experimental insights into the mechanisms underlying the effects of biodiversity and climate change on ecosystem functioning. Abstract : How plant communities and soil microorganisms interact to determine the multifunctionality under climate change is poorly known. We evaluated, using an experimental approach, how simulated climate change (warming and rainfall reduction) and initial plant species richness affect plant functional structure and soil microorganisms. Also, we assessed how all these factors affect, directly and indirectly, soil multifunctionality. Warming selected for the larger and most productive plant species, increasing the average size in the communities and leading to reductions in functional plant diversity. These changes increased the total abundance of bacteria that, in turn, increased that of protists, ultimately promoting soil multifunctionality.